Customer Purchasing Decisions: The influence of Price and Brand Image: Study in one Muslim industry in Bandung - Istikomah, Nur; Sidharta, Iwan; Herawati, Octaviane; Najwa, Haritsatun (LPPM STMIK Mardira Indonesia, 2024)
This research aims to determine the influence of price and brand image on customer purchase decisions. Additionally, this study seeks to analyze the dominant factor between price and brand image affecting customer purchase decisions in the Muslim clothing industry in Bandung. The research focuses on